FACTORES DEL DELITO DE FEMINICIDIO PARA DETERMINAR LA POLITICA DE CRIMINALIDAD, JUZGADO COLEGIADO, DISTRITO JUDICIAL DE ICA, 2019 - LEÓN LAURENCIO, JOSÉ LUIS (2020)
The legal investigation exposed has the general objective of explaining the factors of the crime of femicide in order to determine the policy of criminality in the Collegiate Court, Ica Judicial District, as well as contextualizing the specific objectives in relation to the dimensions, psychopathological, social and cultural, With a non-experimental, descriptive, cross-sectional and explanatory design, using a non-probabilistic sample, it was made up of 20 files, using the survey and documentary analysis as a technique and the questionnaire consisting of 15 closed questions of a dichotomous and polycotomic nature as well as analyzed all the documentation related to the various files of this court related to femicide. It was determined that the fundamental factors for the commission of crime were the factors related to the psychopathological dimensions related to jealousy with 30%, obsession with re love relationship with the partner 21%% and mistrust with 15 %%, making a total of 66% this psychopathological dimension; In this sense, this legal work will analyze in greater depth the cause of jealousy, it will only take care of one of the causes such as jealousy, because in view of this, it will be necessary to determine what are the causes of jealousy and what are its causes. own characteristics that are developed then the existing link with feminicide must be analyzed, concluding in relation to the objectives, that the fundamental factor in the commission of crimes by feminicide are psychopathological, followed by social factors in relation to the customs and ways of life and submission of women, followed by the cultural dimension in relation to machismo that is presented for this commission of crimes Likewise, this investigation not only analyzes the crime in its doctrinal but also procedural form, determined the legal actions or procedures that the victim must carry out in the context of Peruvian legal regulations. Based on this, the possible recommendations that could be implemented for the improvement or solution of this problem regarding femicide are reached.